The social and political aspects of food surplus. Issue 1 (1st January 2017) - Hastorf, Christine A.; Foxhall, Lin
ABSTRACT: This article looks at how surplus is not only an economic reality but a state of mind, created by and reflecting the social and political relations of a group, by considering examples of historic and prehistoric food surplus. The state of one's surplus is not just what one stores, but also how others see it and think about it. Individuals are not alone, but always think of their surplus within a larger network of social and political interactions with others who are also storing food as well as within the rules for access. These networks have been considered safety nets by archaeologists, but often, as with many situations today, the populace does not have access to the safety net. Two case studies illustrate the dynamics and differences of this constructed side of food surplus.